2010
DOI: 10.5694/j.1326-5377.2010.tb03426.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adult patients hospitalised with pandemic (H1N1) 2009 influenza and seasonal influenza during the “PROTECT” phase of the pandemic response

Abstract: Objective: To compare the patient characteristics, clinical features and outcomes of adult patients hospitalised with pandemic (H1N1) 2009 influenza and seasonal influenza. Design and setting: Retrospective medical record review of all patients admitted to Liverpool Hospital, Sydney, with laboratory‐confirmed influenza from the initiation of the “PROTECT” phase of the pandemic response on 17 June until the end of our study period on 31 July 2009. Main outcome measures: Severity of illness; requirement for admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 7 publications
4
39
4
Order By: Relevance
“…In contrast to the study conducted by Chang et al , 9 which is also a concurrent analysis of hospitalised patients with pandemic A (H1N1) and seasonal influenza, our study found several differences in the clinical features of patients with pandemic A (H1N1) and seasonal influenza. This may be because our study included more patients, allowing detection of smaller differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the study conducted by Chang et al , 9 which is also a concurrent analysis of hospitalised patients with pandemic A (H1N1) and seasonal influenza, our study found several differences in the clinical features of patients with pandemic A (H1N1) and seasonal influenza. This may be because our study included more patients, allowing detection of smaller differences.…”
Section: Discussioncontrasting
confidence: 99%
“…There have been two studies in the southern hemisphere which concurrently compared pandemic A (H1N1) and seasonal influenza. The first study, conducted in Sydney, Australia, found that patients with pandemic A (H1N1) were younger and less likely to be immunocompromised than those with seasonal influenza 9. In that study, there were no statistically significant differences in the clinical features and outcome between pandemic A (H1N1) and seasonal influenza.…”
Section: Introductionmentioning
confidence: 96%
“…These findings differ from those of other studies 9,10. The difference may be attributed, at least in part, to the time of investigation.…”
contrasting
confidence: 93%
“…The 4.3% (22/511) patients reported pregnancy [Table 4] in this study among A (H1N1) influenza patients was higher than the expected prevalence in the general population (1%),[28] in contrast, 7% was reported in US,[19] 11% in New Zealand,[23] and 16.7% in Australia. [29] During periods of seasonal influenza and past pandemics, pregnant women have been at higher risk for influenza associated morbidity and mortality. [28293031]…”
Section: Discussionmentioning
confidence: 99%
“…[29] During periods of seasonal influenza and past pandemics, pregnant women have been at higher risk for influenza associated morbidity and mortality. [28293031]…”
Section: Discussionmentioning
confidence: 99%